Implementation of Financial Management at PT Mahkota Abadi Bogor (Sharia Financial Management Analysis) - Ardiyanti, Anita; Murniadi, Murniadi; Imraan, Mohd (The International Journal of Education Management and Sociology, 2024)
The purpose of this research is to determine the management functions at PT Mahkota Abadi in Bogor, and to analyze the functions of sharia financial management at PT Mahkota Abadi in Bogor. This research method is descriptive qualitative with a phenomenological approach, research data is obtained from primary data, namely sources in the company which include managers, department heads and company employees, secondary data comes from company data or financial reports. The data analysis techniques used are data reduction techniques, data presentation, and drawing conclusions. The results of this research are that PT Mahkota Abadi implements management functions well in the company, as seen in the performance of its employees who already understand their duties and responsibilities, as well as financial planning made by the heads of each division in detail and thoroughly in accordance with operational needs. company. And have social responsibility in the form of providing assistance to the surrounding community, while running the company, do not do anything that is contrary to the rules and principles of sharia, for example actions that can harm other parties or usury in financial transactions but are carried out fairly and honestly, so that in transactions both parties parties gain benefits.